Cardiovascular disease and COVID-19, a deadly combination: A review about direct and indirect impact of a pandemic - Vidal-Perez, Rafael; Brandão, Mariana; Pazdernik, Michal; Kresoja, Karl-Patrik; Carpenito, Myriam; Maeda, Shingo; Casado-Arroyo, Rubén; Muscoli, Saverio; Pöss, Janine; Fontes-Carvalho, Ricardo; Vazquez-Rodriguez, Jose Manuel (World journal of clinical cases, 2022)
Coronavirus disease 2019 (COVID-19) is known to present with respiratory symptoms, which can lead to severe pneumonia and respiratory failure. However, it can have multisystem complications such as cardiovascular manifestations. The cardiovascular manifestations reported comprise myocarditis, cardiogenic shock, arrhythmias, pulmonary embolism, deep vein embolism, acute heart failure, and myocardial infarction. There is also an indirect impact of the pandemic on the management of cardiovascular care that has been shown clearly in multiple publications. In this review, we summarize the deadly relation of COVID-19 with cardiovascular events and the wider impact on several cardiovascular care areas by the pandemic situation.
Keywords: Cardiovascular diseases; Pandemic; COVID-19; Heart failure; Telemedicine; Prognosis